Effects of stigmatizing media coverage on stigma measures, self-esteem, and affectivity in persons with depression - an experimental controlled trial - Göpfert, Nele Cornelia; Heydendorff, Steffen Conrad von; Dreßing, Harald; Bailer, Josef (BMC psychiatry, 2019)
Stigmatization of people with mental illness is still a significant problem even in Western society. Media is an important vector for public messaging that may lead to stigma (and potentially counteract it). There is an ongoing debate about the impact of news with potentially stigmatizing content on people with depression. This experimental study aimed at investigating the direct effects media reporting could have on people with depression, namely, higher levels of stigma attitudes and negative affect, as well as lower levels of self-esteem and positive affect.
Gesehen am 20.09.2019